The Role of Teachers and Communication Information Technology (ICT) Media in the Implementation of Mathematics Learning in the Digital Age - Vidyastuti, Annisa Nurina; Darmayanti, Rani; Sugianto, Rahmad (Universitas Islam Raden Intan Lampung, INDONESIA, 2018)
The current era of modernization has brought the Indonesian nation forward in the development of science and technology. This is marked by the existence of information and communication that spreads quickly in life, including in the world of education. Along with the development of ICT, one must also be able to adjust, sort, and utilize the development of information and communication so that it can make a positive contribution to students. The purpose of this study was to describe the role of teachers and information communication technology (ICT) media in the implementation of mathematics learning in the Digital Age. This research is a literature study with a descriptive qualitative research type with a literature review that seeks to describe the role of educational innovation in digital technology-based learning. In this study, the authors used various written sources such as articles, journals, and documents that were relevant to the studies in this study. This Literature Study focuses on the role of a teacher in learning mathematics, digital technology in education, and the use of technology in education, as well as digital-based learning media. Learning has an important role in efforts to improve the quality of education, so that learning can bring meaning and benefits to students. The conclusion in this paper is that ICT mastery is an indicator of a teacher's competence. The selection and use of ICT media must be correlated with learning and adapted to the needs of learning activities